MUSIK DALAM WACANA KEAGAMAAN: SEBUAH UPAYA KONTEKSTUALISASI HADIS - fauzi, ahmad (Mazalat: Jurnal Pemikiran Islam, 2023)
Discourse on music has always been an interesting issue in Islam. Some scholars forbid it, but others allow it. These differences are caused by different understandings of religious texts, especially hadiths that talk about music. The hadith which is indicated forbidding music is the hadith narrated by Imam Bukhari. However, a narrator is considered dhaif. Meanwhile, another hadiths which have substantially almost same do not clearly prohibit it because it is explaining the prohibition of khamr, not music. When associated with other arguments, it can be understood that there are three 'illat or reasons why music is prohibited. First, playing music is synonymous with the habits of people who do a sin. Second, it resembles a devil's flute. Third, it is included useless words. Thus, the contextualization of the hadiths related to music is that it is allowed if the lyrics are not dirty and invite disobedience to Allah. Music can also be used as a method of preaching, uplifting and spreading kindness.